Chapter 1 The puzzling resilience of authoritarian party dominance - Washida, Hidekuni (Taylor & Francis, 2023)
Numerous studies have explored why some autocracies endure but others do not. Although they argue that party-based, parliamentary autocracies are relatively resilient, even during multiparty elections, because of the credible power/benefit-sharing among elites and masses, there have been insufficient studies to examine the exact mechanism of distributive politics. This book fills this gap by systematically analyzing the patterns of resource distribution (budgets, posts, and seats) in the key case of party dominance - Malaysia under the Barisan Nasional. This chapter explains the merits of focusing on this case, the shortcomings of existing arguments, and the plan of the following chapters.